Exploring the Fundamental Factors Behind Algal-Bacterial Symbiosis and Their Impact on Ecological Interactions - Sun, Li; Lei, Yongjia; Li, Hui (Frontiers in Environmental Science, 2022)
This study focused on the important factors, including light intensity, light/dark cycles, and the biomass of algae/bacteria to explore the relationship between algae and bacteria, which aimed to obtain the optimal performance in the algae-sludge membrane bioreactor (AS-MBR). It was found that the 3000 lux was considered to be the appropriate light intensity that could improve the algal biomass and nitrogen removal among the chosen light intensities. Further results analysis indicated that a higher or lower light intensity could not simultaneously promote the algal energy absorption and nitrifying bacteria activity. Moreover, the highest average growth rate of algae (0.16 mg/L d-1) and the removal efficiency of NH4+-N (96.4±1.5%) were both observed during the 12-h-Light/12-h-Dark cycle, respectively. Meantime, the appropriate algal proportion would mitigate the membrane fouling compared with the conventional MBR. The mechanism investigation suggested that light intensity, light-dark cycle, and algae proportion were significantly associated with the algal photosynthesis (key proteins, chromophores, and nucleic acids), the characteristics of functional bacteria and the underlying cognition of cell-to-cell signaling between algae and bacteria, that would further influence the reactor performance.